Funkcionalna električna stimulacija pri urjenju hoje - Bajd, Tadej (Rehabilitacija (Ljubljana), 2011)
We briefly review the peroneal functional electrical stimulation (FES) applications in gait training of subjects with incomplete lesion to the spinalcord as introduced by the researchers from Ljubljana. Next, we describe the results of international studies on neurorehabilitation gait relevant for evidence based rehabilitation. The studies include the comparisons of FES, robot, and orthosis-assisted walking. In conclusion, some thoughts on future development in the field of FES are given.
Keywords: električna stimulacija; hoja; hrbtenjača; poškodbe